PERBAIKAN INFRASTRUKTUR AIR BERSIH DAN FASILITAS DESA DI GUNUNG BUNDER : MENUJU KESEJAHTERAAN PEDESAAN - Dwi Kristanto; Yuni Kasmawati; Muhammad Jusmansyah; Aris Wahyu Kuncoro; Said Said; Maruji Pakpahan (Jurnal Padamu Negeri, 2024)
Community Service Activities (PKM) with the theme "Improvement of Clean Water Infrastructure and Village Facilities in Gunung Bunder: Towards Rural Welfare" aims to improve access to clean water and improve village facilities in the area to enhance the welfare of rural residents. This PKM involves collaboration between academics, students, local government, and the community in designing and implementing various infrastructure improvement programs. The methods used in this activity include field surveys, interviews with the community, data analysis, and active participation from various stakeholders. The results of this PKM show a significant improvement in access to clean water and the improvement of village facilities in Gunung Bunder. The impact of these efforts is not only seen in the physical improvement of infrastructure but also in the improvement of the welfare and quality of life of the community. Through a participatory and sustainable approach, the PKM "Improvement of Clean Water Infrastructure and Village Facilities in Gunung Bunder" has successfully created positive changes in efforts to achieve rural welfare. This activity is also expected to inspire similar efforts in other rural areas and serve as a first step in building a more independent, sustainable, and prosperous village.